Dampak Pemberitaan Infotainment di Televisi dalam Industrialisasi Media terhadap Perilaku Etika di Masyarakat - Karlina, Luluk (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Impact of globalization to ownership of media one of them is the happening of emulation of free market where them owning big capital progressively easy to to buy small medias or local medias. Tendency of media to be more make account of business made by a reason of to owner for the shake of continuity of their business. On that account up to now event of infotainment still displayed by because still enthused by society and represent biggest production to media industry. The hoisterous of infotainment in the form of news concerning artist various media, representing requirement of media industry basically to get to inclusion to its company. Impact of infotainment in the reality have major effect in behavior of society. Life style of hedonis that happened society represent one of the example of how society imitate artist. Behavioral negativity from artist become news materials of infotainment presented is possible to forward sensation without effect and ethics from Indonesian nation culture. Importance of media industry for the meraup of advantage leave for behind with journalist idealism to obey from code of ethics. Journalist claimed to look for to news of semenarik. Need control in the form of order arranging event of infotainment break the rules in order not to in reporting on gossip and ignominy. Coherent action to adhere code of etik law and require to be conducted for the benefit of take care of moral and ethics in society.